2008
DOI: 10.1097/dad.0b013e318164cf4b
|View full text |Cite
|
Sign up to set email alerts
|

Hematidrosis: A Pathologic Process or Stigmata. A Case Report With Comprehensive Histopathologic and Immunoperoxidase Studies

Abstract: Cases of hematidrosis (bloody sweat) are extremely rare. This disease has been described in various terms and has been often tied to religious belief as stigmatization. We report a typical patient with hematidrosis in a 14-year-old girl who frequently bled from her scalp and palms, and, occasionally, from trunk, soles, and legs. The bloody sweat from her scalp contained all blood elements. Immediate biopsy after there was bleeding on her scalp showed multiple blood-filled spaces that opened directly into the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 7 publications
8
99
1
1
Order By: Relevance
“…The bleeding may occur from any area of unbroken skin anywhere in the body and may be unilateral, bilateral or symmetrical. It may be limited to a specific area or generalised 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The bleeding may occur from any area of unbroken skin anywhere in the body and may be unilateral, bilateral or symmetrical. It may be limited to a specific area or generalised 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…solving clinical problems in blood diseases including hands, feet, arms, and legs. Twinkle exhibited no apparent stress preceding or during her bleeding episodes, and it did not appear that her bleeding was emanating from hair follicles; however, based on prior case reports, neither of these factors is present in all cases [2,3]. Interestingly, hematidrosis is frequently determined to be a diagnosis in clinical scenarios where a serious diagnostic consideration is self inflicted bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells may be observed within the follicular lumens on histopathology. The bloody sweat excretion can occur in situations of stress or exertion, and can be visualized on physical examination as emanating from the hair follicles [2]. A recent report by Wang et al found only minor extravasation of red blood cells and loosening of the connective tissue on histopathology in a 13-year-old female with hematidrosis [3], and a recent case in an 18-year-old female demonstrated no anatomic anomalies [4].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, scientific explanations have been proposed in multiple papers. The exact cause of this phenomenon is not completely understood, but activation of the sympathetic nervous system has been implicated [1]. In cases of extreme anxiety, the net--like form of multiple blood vessels that feed the sweat glands constricts and then dilates to the point of rupture.…”
Section: Introductionmentioning
confidence: 99%